High glucose reduces anti-tumor activity of aromatase inhibitors in a hormone-dependent breast cancer cell model - Kamila Boszkiewicz; Agnieszka Piwowar (Polskie Towarzystwo Farmaceutyczne, 2023)
One third of breast cancer patients also suffer from diabetes, which is associated with a 40% higher risk of mortality. Patients undergoing anti-cancer treatment are also exposed to xenoestrogens present in everyday life, which may affect the effectiveness of the therapies used. The purpose of our study was to analyzed the effect of metalloestrogens (Al, Cr[III]) on the effectiveness of aromatase inhibitors (AIs) under high glucose conditions prevailing in the cellular model. On two human breast cancer cell lines-MCF-7 and MCF-7/DOX-a cell viability assay, a flow cytometer analysis of apoptosis, and protein activity of BAX, Bcl-2, and VEGF-A by ELISA were carried out. Results were analyzed using one-way ANOVA, followed post hoc by Tukey's multiple comparisons tests. High glucose conditions reduced the effectiveness of AIs in both cell lines (decreased cytotoxicity, inhibition of apoptosis, increase in Bcl-2/BAX ratio and angiogenesis), regardless of the combination with metalloestrogens. Hyperglycemia may affect the effectiveness of AIs to a greater extent than metalloestrogens alone - the activity of drugs in the presence of high glucose concentrations was significantly lower, regardless of the combination with metalloestrogens, which indicates the key role of hyperglycemia in attenuating their activity. Therefore controlling hyperglycemia and individualized treatment regimens in cancer patients with diabetes may have important therapeutic implications.